2022
DOI: 10.1088/1361-6668/ac4f6a
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the effect of structural defects from hydride precipitation on superconducting properties of high purity SRF cavity Nb using magneto-optical and electron imaging methods

Abstract: Nb is an elemental superconductor with a critical temperature of 9.3 K and is widely used to fabricate superconducting radiofrequency (SRF) cavities for particle accelerators. However, microstructural defects in Nb, such as grain boundaries and dislocations, can act as pinning centers for magnetic flux that can degrade SRF cavity performance. Hydrogen contamination is also detrimental to SRF cavity performance due to the formation of normal conducting hydrides during cool down. In this study, disc shaped Nb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…At H c1 < H a < H s the Meissner state remains metastable due to the Bean-Livingstron barrier [22]. Many magneto-optical imaging investigations of type-II superconductors [229][230][231][232] have revealed premature local penetration of vortices at grain boundaries and other materials and topographic defects at the surface [54][55][56][57]. In turn, TDGL and nonlinear electrodynamic simulations have shown that surface defects can reduce the penetration field [233][234][235] and cause flux jets [236,237] being precursors of themomagnetic avalanches.…”
Section: Surface Nanostructuringmentioning
confidence: 99%
“…At H c1 < H a < H s the Meissner state remains metastable due to the Bean-Livingstron barrier [22]. Many magneto-optical imaging investigations of type-II superconductors [229][230][231][232] have revealed premature local penetration of vortices at grain boundaries and other materials and topographic defects at the surface [54][55][56][57]. In turn, TDGL and nonlinear electrodynamic simulations have shown that surface defects can reduce the penetration field [233][234][235] and cause flux jets [236,237] being precursors of themomagnetic avalanches.…”
Section: Surface Nanostructuringmentioning
confidence: 99%
“…Test results have been published in [13] and were not really satisfactory because of Q-disease: the presence of a significant amount of hydrogen in niobium material leads to the formation of niobium hydride precipitates when exposed to low temperatures typically between 50 and 150 K [28]. These niobium hydrides are non-superconducting and lead to a strong degradation of the surface resistance [29][30][31]. Thus, the triggering of Q-disease on our samples made the evaluation of the impact of the polishing procedure on the surface resistance not relevant.…”
Section: Step 2: Depollution Stepmentioning
confidence: 99%